PENDIDIKAN KARAKTER ISLAMI DAN PEMBERDAYAAN KEARIFAN LOKAL DALAM PAUD - Syamsul Bachri Thalib (Universitas Negeri Makassar, 2015)
Character education as an effort designed to systematically and continuously to form the personality of students based on noble norms which are upheld highly by society. Cultural factors and social environment including religious values, norms, socio-cultural changes, and the goals or expectations to be achieved which reflected in the social interaction relationship is potentially have an effect and contribution to the character development of students. Therefore, the family-based and the local Islamic wisdom character education should become the main focus from the beginning or from the early childhood. Character values that can be developed include obedient attitudes and behaviors in implementing the values of religion, honesty, discipline, environmental care, social care, and values oriented to the development of noble character. Teachers and education personnels play an important role in stimulating the development of the character and personality of early childhood.